Physiological and metabolic consequences of autophagy deficiency for the management of nitrogen and protein resources in Arabidopsis leaves depending on nitrate availability - Guiboileau, Anne (The New phytologist, 2013)
© 2013 INRA. New Phytologist © 2013 New Phytologist Trust.